Calculation and Research of Transmission Efficiency of Gear with Addendum Modification based on Roll-off Angle - Wang Yixinyu; Tang Jinyuan (Jixie chuandong)
Based on the power method,the roll-off angle is introduced to measure the position of meshing point,and the function relation formula between the modification coefficient and meshing efficiency is derived.The calculation formulation of modification coefficient of the maximum transmission efficiency is put forward through deriving the relation on the basis of extremism value principle for functions.Through the comparing with the experimental results of available literatures,can get to know that the numerical results of the calculation of modification coefficient and transmission efficiency are in good agreement with the experimental results of available literatures.A base for quantitative calculation of the initiative design of gear with addendum modification transmission efficiency is provided through the research work,and it has a certain reference value to the research and application for the gear with addendum modification.